ANALYSIS OF THE INFLUENCE OF PRODUCT, PRICE, DISTRIBUTION, AND PROMOTION ON CONSUMER PURCHASE DECISIONS USING GO FOOD APPLICATION DURING THE COVID PANDEMIC 2021 - Dwi Supraptiningsih, Joelianti (Dinasti Publisher, 2021)
This study at to analyze the effect of product, price, place, and promotion on consumer purchasing decisions uses the Go Food application during the covid pandemic 2021 The research methodology used quantitative method with cross section data and primary data obtained from questionnaires. Mechanical sampling uses purposive sampling method. The data analysis technique used is multiple linear regression to test the validity, reliability test, normality test, classic assumption test (multicollinearity test, heteroscedasticity test) and hypothesis testing t-statistics and f-statistics to examine the effect together with a significance level of 5%. The results of this study showed that in partial variables of Product, Price, Place, and Promotion have a positive impact and significant impact on consumer purchasing decisions using the Go Food application. Meanwhile, independent variables of Product, Price, Place, and Promotion simultaneously have a significant relationship to the dependent variables, on consumer purchasing decisions using the Go Food application. Coefficient of determination from this study shows 83.01%. It shows that the variation of the independent variables are Product, Price, Place, and Promotion is able to explain the rise and fall of the dependent variable variation on consumer purchasing decisions using the Go Food application is 83.01%, while the remaining of 16.99% is affected by other independent variables.